Vessel health and preservation: Development and validation of a proactive instrument. Issue 5 (October 2021) - Fiorini, Jacopo; Piredda, Michela; Zaghini, Francesco; Venturini, Giulia; Colella, Sonia; Conti, Fabio; Denton, Andrea; Sili, Alessandro
Abstract: Problem: To preserve vessel health quality, nurses should proactively assess patients' veins and analyse factors related to anatomical characteristics and the intravenous therapy plan. Although many advantages of proactive approach are acknowledged, no tool is available to evaluate variables related to peripheral vein quality and identify those patients at risk of reduction in vessel health quality. Aim: To develop and validate a tool evaluating the risk of vessel quality reduction of patients needing infusion therapy. Methods: Instrument development and validation study was carried out: 280 patients aged 18 years or older, hospitalised for the previous 24–48 hours were enrolled. Instrument face and content validity were analysed. The Receiver-operating characteristic analysis was used to choose the best cut-off; specificity, sensitivity, positive, and negative predictive values were calculated. Findings: The scale score range was 0–50. The best cut-off was identified as a score ≥ 15 (area under curve 0.91), with 95% sensitivity and 72% specificity. A specialist in placement of vascular devices was requested in the first 3 days since admission for at-risk patients. Discussion: The new Vessel Health and Preservation Scale is specific and sensitive in identifying patients at risk of reduction in vessel quality. This study provides nurses with an instrument to preserve their patients' vein health and guarantee them better outcomes. Conclusion: Using the Vessel Health and Preservation Scale at patients' admission enables nurses to proactively preserve vein quality and decide on choosing and positioning the right device or requesting a vascular access specialist.